Comparison of Gram Stain and Pap Smear Procedures in the Diagnosis of Bacterial Vaginosis - Enver Vardar; Izzet Maral; Murat Inal; Özgül Özgüder; Funda Tasli; Hakan Postaci (Hindawi Limited, 2002)
Objective: The purpose of this study was to examine the characteristics of Gram stain versus Pap smear in diagnosis of bacterial vaginosis (BV).